(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article examines the economic efficiency of the innovative development of the viticulture sector in agriculture, as well as the theoretical and practical aspects of introducing “smart agriculture” technologies. The study highlights the opportunities for efficient use of resources, increased productivity, and reduction of production costs through the application of intensive vineyards, drip irrigation systems, digital monitoring, IoT devices, artificial intelligence, and drone technologies in viticulture. Furthermore, the economic impact of digital technologies on water conservation, labor productivity, product quality, and export potential is assessed. The article also analyzes the ongoing reforms aimed at the digital transformation of the viticulture sector in Uzbekistan and proposes practical recommendations for the further development of the industry.